Digital Wildlife Photography. - Gerlach, John and Barbara (Taylor and Francis, 2012)
Using a combination of artistic approach and impeccable technique, professional photographers John and Barbara Gerlach will guide you through the field as you photograph the most intriguing and captivating subjects out in the wild. A sampling of what you'll learn:How to integrate equipment with technique to capture superb wildlife images of birds, mammals, amphibians, and more with an emphasis on precision and speedWhere and how animals can be approached closely enough to photograph wellHow not to disturb the critters around you, depending on envi.